HUBUNGAN ANTARA KONFLIK INTERPERSONAL DENGAN TINGKAT KECEMASAN MAHASISWA - Dilas, Erlangga Alfath Tauhid Dilas; Kristinawati, Wahyuni (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
This study aims to examine the relationship between interpersonal conflict and anxiety levels among university students. The research employed a quantitative method with a correlational approach. A total of 176 active students voluntarily participated in completing the online questionnaires using the Interpersonal Conflict Scale and the Beck Anxiety Inventory (BAI). The results of validity and reliability tests indicated that both the interpersonal conflict scale and the anxiety scale met the criteria for valid and reliable measurement. The assumption test showed that the data were not normally distributed; therefore, Spearman’s rank-order correlation was used for the analysis. The findings revealed a strong and significant positive relationship between interpersonal conflict and anxiety levels (r = 0.868; p < 0.05). Furthermore, simple linear regression analysis showed that interpersonal conflict contributed 62.8% to the variation in students’ anxiety levels. These findings highlight that interpersonal conflict is significantly associated with students’ anxiety.